2017
DOI: 10.1016/j.clon.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of Unknown Primary: a Cancer Registry Study of Factors Affecting Access to Diagnosis

Abstract: The registry classified 7,428 patients as C80, 8,849 as C77-79, and 10,804 as C20. Compared to C20, the number of cases of C80 showed a statistically significant increasing trend with 3 increasing travel time to primary care. Risk also increased strongly with age, and deprivation.Results for C77-C79 were similar to those for C80, except that the travel time to primary care showed no effect. Considering all CUP alone, histological diagnosis significantly declined with travel time to the nearest hospital. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Our survey of seasoned pastoral leaders revealed that they had a lower than average cancer knowledge. This finding is in line with previous studies, which found that overall public knowledge of cancer is poor [23,24]. Yet, an encouraging 73% of church leaders in the present study indicated that they would be interested in trainings to increase their knowledge.…”
Section: Discussionsupporting
confidence: 80%
“…Our survey of seasoned pastoral leaders revealed that they had a lower than average cancer knowledge. This finding is in line with previous studies, which found that overall public knowledge of cancer is poor [23,24]. Yet, an encouraging 73% of church leaders in the present study indicated that they would be interested in trainings to increase their knowledge.…”
Section: Discussionsupporting
confidence: 80%
“…During the observation time this study was conducted, Medicare did not cover genetic/molecular tests. Thus, financial access to molecular tests may have been unavailable to many patients [30]. Recently, commercial tests of gene profiling microarrays became available for the diagnosis of CUP.…”
Section: Discussionmentioning
confidence: 99%
“…This allowed us to construct a comprehensive picture of people's health service use prior to cancer diagnosis. While our sample size is one of the largest population-based studies of people with CUP [8,9], it is modest. As a result, we may have had insufficient power to detect an association with some health services, and where we did, the confidence intervals are wide.…”
Section: Plos Onementioning
confidence: 99%
“…While a diagnosis of CUP ideally should be limited to people with a histological confirmation of metastatic cancer, in whom thorough testing has failed to identify the site of the primary tumor, people registered with a diagnosis of CUP in population-based cancer registries are heterogeneous, with many people receiving a diagnosis based on clinical examination only. [4,5,[8][9][10][11] Thus, it is difficult to compare population-based studies of registry-notified CUP to cases series of "true CUP" cases, who have received exhaustive investigations.…”
Section: Introductionmentioning
confidence: 99%